The Complexity of Contextual Meaning in Political Texts on X - Ni Ketut Sri Rahayuni; I Wayan Pastika; I Made Netra; Ketut Artawa (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study investigates the complexity of contextual meaning in political texts posted by public figures on the social media platform X (formerly Twitter). Grounded in Halliday and Hasan’s theory of situational context and Searle’s speech act theory, the research analyzes how political utterances function through locutionary, illocutionary, and perlocutionary acts. The data, drawn from tweets during the 2024 Indonesian presidential election period, were collected using documentation and structured observation methods. The findings indicate that political texts on X are highly layered, combining explicit facts with implicit criticism, ideological stance, and persuasive strategies. Through representative, expressive, and directive speech acts, public figures construct meaning that influences public perception, evokes emotional responses, and fosters political alignment. This study contributes to the understanding of digital political discourse by highlighting how pragmatic strategies shape the interpretation of meaning in online political communication.